Microstructure, mechanical and tribological properties of oxide dispersion strengthened CoCrFeMnNi high-entropy alloys fabricated by powder metallurgy - Nagarjuna, Cheenepalli; Sharma, Ashutosh; Lee, Kwan; Hong, Soon Jik; Ahn, Byungmin (Journal of Materials Research and Technology, 2023)
Developing materials with superior strength and wear resistance has always drawn challenging research for advanced engineering applications. Herein, considerable efforts have been devoted to enhancing the strength and wear resistance of face-centered cubic (FCC)-structured CoCrFeMnNi high entropy alloy (HEA) by incorporating HfO2 nanoparticles (NPs) through a powder metallurgy approach. The phase composition, microstructure, mechanical, and tribological properties of HEA composites were investigated. The XRD results reveal that the composite powders consisted of the FCC solid solution along with minor HfO2 phases. In addition, sintered HEAs showed the major FCC phase along with minor Cr-rich and HfO2 phases. Microscopic results confirmed the uniform distribution of HfO2 NPs throughout the matrix during the milling process. With increasing HfO2 contents, the hardness of the HEAs increased from 270 ± 10 to 520 ± 10 HV, while the compressive yield strength increased from 370 to 1500 MPa, due to dispersion and grain boundary strengthening effects. Furthermore, composite HEAs showed a decrease in coefficient of friction and wear rates with increasing HfO2 content due to increased surface hardness and transition in wear mechanism from severe wear to mild abrasive wear. The present study demonstrates the feasibility of producing high-performance oxide dispersion-strengthened HEAs for advanced structural applications.
Keywords: Advanced engineerings; Alloy composites; Dispersion strengthening; Engineering applications; Face-centred cubic; High entropy alloys; Mechanical and tribological properties; Microstructure mechanical properties; Oxide dispersion strengthened; XRD; Dispersion strengthening; High entropy alloys; Mechanical properties; Microstructural evolution; Tribology